The Relationship Between Organizational Justice and Employee Performance: The Mediating Role of Job Satisfaction in Private Banks of Balochistan - Sadaqat, Madiha; Shafiq, Muhammad; Mukhtar, Uzma (Pakistan Languages and Humanities Review, 2025)
This study investigates the relationships between organizational justice (OJ), job satisfaction (JS), and employee performance (EP). It also explores the mediating role of job satisfaction in the link between organizational justice and employee performance. Organizational justice, encompassing distributive, procedural, and interactional justice, is a critical factor in fostering employee engagement and productivity in social systems like banks. Rooted in Social Exchange Theory, this study addresses a research gap in developing regions, specifically the banking sector of Balochistan, where prior research is limited. A quantitative approach was used, with data collected from 200 employees across 14 private banks in Quetta, Balochistan, using structured questionnaires. The study tested its hypotheses using regression and mediation analysis with Hayes’ PROCESS macro. Employee performance was assessed using supervisor ratings to reduce common method bias. The findings indicate that all three dimensions of organizational justice significantly improve employee performance, both directly and indirectly, through job satisfaction. Job satisfaction was found to partially mediate the relationship, with approximately 31% of the effect for distributive justice and about 41% for both procedural and interactional justice being transmitted through satisfaction. The study recommends that private banks in Balochistan focus on fairness in their decision-making, reward systems, and interpersonal treatment. Implementing transparent procedures and training supervisors in fair practices can enhance job satisfaction and, in turn, drive higher levels of employee performance.